If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(a) + -3a = 0 Multiply a * a a2 + -3a = 0 Reorder the terms: -3a + a2 = 0 Solving -3a + a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), 'a'. a(-3 + a) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(-3 + a)' equal to zero and attempt to solve: Simplifying -3 + a = 0 Solving -3 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + a = 0 + 3 Combine like terms: -3 + 3 = 0 0 + a = 0 + 3 a = 0 + 3 Combine like terms: 0 + 3 = 3 a = 3 Simplifying a = 3Solution
a = {0, 3}
| -8-6=10-9x | | 2x-2=11x+65 | | 8p+5q-1=0 | | y=-5x+15 | | 6+4x=39-x | | 6x+19=16+4 | | 6x+19=10x+4 | | 2(6-x)-11=5(3x+7) | | a=22b+c | | 10-x=21/4 | | (1/x)+(1/x+5)=9/100 | | 32445/75x^2+y^445 | | 4x+23=5x+17 | | 5x+29=10x+4 | | 3x-4x=x-2 | | 19x-2=0 | | lg(x+4)-lg(x-5)=1 | | 8c=4d | | E=x^3-5x^2+8x-4 | | 179=18 | | 3x-5y=73 | | 15x^4+15x^2+x^2+1= | | 8x^2-392=0 | | 5x^2-18x=-k | | 6x^5+36x= | | x^2-2304=0 | | 3(n+3)+8(n+6)= | | -5x-3.2=-3x+3.6 | | 4x+11=x+41 | | 127-7x=29X+23 | | -132-8=7x+18 | | 5X-9=149-37X |